Монгол Улсын Ерөнхийлөгч Н.Энхбаяр, Бүгд Найрамдах Хорват Улсын Ерөнхийлөгч Степан Месич нарын хамтарсан мэдэгдэл (Journal of International Studies, 2008)
English title: Joint declaration of the N.Enkhbayar, President of the Mongolia and Stepan Mesic, President of the Republic of the Croatia